Kandungan β-Karoten dan Produksi Plasma Nutfah Ubi Jalar Lokal Lampung pada Umur Panen yang Berbeda: β-Carotene Content and Germplasm Production of Local Sweet Potatoes in Lampung at Different Harvest Ages - Ratna Dewi; Ari Wahyuni; Hasan Basri (Politeknik Negeri Lampung, 2022)
Sweet potato (Ipomoea batatas L.) with orange flesh enriched with β-carotene andvitamin A can help combat vitamin A deficiency and malnutrition, especially forcommunities in developing countries. The purpose of this study is to select local sweetpotatoes from Lampung which contain β-carotene and to determine an appropriate harvestage to obtain high β-carotene content and production. The study was conducted at theLampung State Polytechnic using a randomized block design (RAK) repeated 2 times.The treatments consisted of 30 genotypes of sweet potato germplasm and 2 harvest ages(3 months after planting and 4 months after planting). The 30 genotypes were selectedbased on flesh color (yellow to dark orange), then tested for β-carotene content andproduction at 3 months and 4 months of harvest. The results showed that from 30genotypes, there were 16 genotypes that had yellow to dark orange flesh color. Thecontent of β-carotene, tuber weight per plant, and number of tubers per plant were higherat 4 months harvest than 3 months harvest. The LPG-01 genotype (Local Lampung) at 3months of harvest had a higher β-carotene content than the other genotypes, which was1,902 µg /100g, while at 4 months the β-carotene content was almost equivalent to theBeta-1 genotype, but higher when compared with other genotypes with 40,493 µg /100g.Genotype of LPG 01 had tuber weight (1,191.90 g per plant) and the number of tubers(5.63 bulbs per plant) higher than the other genotypes. Key words: β-carotene, production, sweet potato, harvest age.